Pelatihan penyusunan modul pembelajaran bahasa Inggris berbasis HOTS bagi guru-guru MGMP bahasa Inggris SMP kota Padang Panjang - Nofrina Eka Putri; Desvalini Anwar; Eko Purnomo (Universitas Negeri Padang, 2022)
In the last few years, there have been a large number of trainings or professional developments carried out to enhance teachers’competence in formulating HOTS-based-test items. These phenomena then seem to put aside the capability of designing and managing classroom activities to develop students’ higher order thinking skills (HOTS). In fact, the latter is essentially needed to prepare students with knowedge and skill to solve problems given in the test. In addition, it is likely unreasonable to administer a HOTS test to those who have never attended a HOTS class. This article then is intended to describe how a training on designing HOTS – based learning module in Junior High Schools was carried out to help teachers to conduct a HOTS-based class. The training and coaching were given to 26 of 35 teachers under the auspices of English Teacher Association in Kota Padang Panjang. Prior to the program, those who were willing to take a part were required to fill in a form of commitment confirming that they have to fully join 36 hours of training and submit a HOTS-based learning module for one meeting at the end. The instructors invited to the program were those having specialties in curriculum design and pedagogical competence. The results of the program show that most of the teachers are able to create a HOTS-based learning module to support learning process after they get some feedbacks and guidance from the instructors.